KAJIAN TIGA RUANG PSIKIS LACAN PADA NARATIF FILM IVANNA (2022) KARYA KIMO STAMBOEL - Sari, Annisa Rachmatika; Wati, Wahyu Utami (TEXTURE Art and Culture Journal, 2024)
Jacques Lacan divides the human psychic area or subject into three parts, namely The Real, The Imaginary, and The Symbolic. In The Ivanna by Kimo Stamboel, Ivanna passes through these three rooms as a ghost who is looking for her head. The Ivanna tells about the terror of the ghost of Ivanna, who suffered a tragic death because she was killed by Japanese soldiers. This research uses a qualitative descriptive method that processes selected scenes in the film Ivanna for analysis to find three psychic spaces that Ivanna passes through as a head-seeking ghost. The Real is experienced when Ivanna's ghostly body is destroyed, thrown in a well, and burned. Ivanna experienced The Imaginary when Ambar saw a projection on the wall regarding Ivanna's past. Ambar, who can translate the meaning of the projections on the wall, finds Ivanna's demands, in the form of bodily integrity. Meanwhile, Ivanna goes through The Symbolic while hunting for the heads of people living in a nursing home. Ivanna got her wish, but because the head she took did not match her wishes, she continued hunting for new heads